2021
DOI: 10.1002/jia2.25655
|View full text |Cite
|
Sign up to set email alerts
|

Subtype‐specific differences in transmission cluster dynamics of HIV‐1 B and CRF01_AE in New South Wales, Australia

Abstract: Introduction The human immunodeficiency virus 1 (HIV‐1) pandemic is characterized by numerous distinct sub‐epidemics (clusters) that continually fuel local transmission. The aims of this study were to identify active growing clusters, to understand which factors most influence the transmission dynamics, how these vary between different subtypes and how this information might contribute to effective public health responses. Methods We used HIV‐1 genomic sequence data linked to demographic factors that accounted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Our analysis revealed that the transmission network of CRF01_AE in Japan has become more complex, comprizing predominantly MSM clusters along with persisting heterosexual/IDU-related clusters. This finding was consistent with a previous study from Australia, which is in the same Western Pacific region (Di Giallonardo et al, 2021). However, at the time of our study, it was not applicable to the European region, where heterosexuals still dominate the transmission network of CRF01_AE (Alexiev et al, 2021;Esbjornsson et al, 2016).…”
Section: The Transmission Network Of Crf01_ae In Japan Has Become More Complexsupporting
confidence: 92%
“…Our analysis revealed that the transmission network of CRF01_AE in Japan has become more complex, comprizing predominantly MSM clusters along with persisting heterosexual/IDU-related clusters. This finding was consistent with a previous study from Australia, which is in the same Western Pacific region (Di Giallonardo et al, 2021). However, at the time of our study, it was not applicable to the European region, where heterosexuals still dominate the transmission network of CRF01_AE (Alexiev et al, 2021;Esbjornsson et al, 2016).…”
Section: The Transmission Network Of Crf01_ae In Japan Has Become More Complexsupporting
confidence: 92%
“…Descriptive epidemiology of the national AIDS surveillance (NAS) in Japan showed that compared to individuals newly diagnosed with HIV without AIDS‐defining illnesses, those newly diagnosed with HIV and AIDS‐defining illnesses were more likely to be older, heterosexual and from non‐urban areas [ 10 ]. Besides demographics, hepatitis B or C co‐infections [ 19 , 20 ], HIV‐1 subtypes [ 21 , 22 , 23 ] and clustering based on nucleotide sequences [ 24 , 25 ] may be associated with late diagnosis, but this information is not included in the NAS. To our knowledge, no large‐scale nationwide study has revealed the association of the aforementioned factors with late HIV diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…An early study also reported that MSM transmission was be the main risk factor for transmission clusters. 39 Besides, as the characteristics of convenient transportation and mobility of downtown, which can lead to the further rapid spread of CRF07_BC in this area, further confirming that attention should be paid to the MSM, especially those live in downtown. We can continue to use the internet to carry out continuous online health education, condom promotion, AIDS counseling, mobilization testing and other services for MSM in Guangyuan, and even consider promoting pre-exposure prophylactics and other measures, so as to reduce the HIV transmission among MSM.…”
Section: Discussionmentioning
confidence: 83%